2016
DOI: 10.1155/2016/3458965
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Impact of Media in Controlling the Diseases with a Piecewise Transmission Rate

Abstract: An epidemic model with media is proposed to describe the spread of infectious diseases in a given region. A piecewise continuous transmission rate is introduced to describe that the media has its effect when the number of the infected exceeds a certain critical level. Furthermore, it is assumed that the impact of the media on the contact transmission is described by an exponential function.Stability analysis of the model shows that the disease-free equilibrium is globally asymptotically stable if the basic rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To find sufficient conditions for the uniqueness of a positive solution of (3.4), we follow the work of Lie et al cited in [30], which provides that…”
Section: Model Developmentmentioning
confidence: 99%
“…To find sufficient conditions for the uniqueness of a positive solution of (3.4), we follow the work of Lie et al cited in [30], which provides that…”
Section: Model Developmentmentioning
confidence: 99%
“…Later on, some authors studied the effects of media coverage on the spread of infectious diseases [16]. Recently, Li et al [17] proposed an epidemic model with media to describe the spread of infectious diseases in a given region. They found that media coverage plays an important role in controlling the spread of the disease.…”
Section: Alwan and Satarmentioning
confidence: 99%
“…To explore this underlying complex interaction, we construct the model with Gompertz's Low incorporates individuals different and limited ability to break down or deconstruct complex issues or situations [33] . Unlike similar studies [ 34 , 35 ], our model also considers that public mass media commonly do not function when there are few infected people at the early stages of the disease's prevalence. Simultaneously, we build a function verified some effect of free-riding, altruism and immunity escaping abilities in making vaccination decisions following the benefit-cost analysis.…”
Section: Introductionmentioning
confidence: 99%